PERUBAHAN IKLIM DAN PERDAGANGAN KARBON DARI PENURUNAN EMISI GAS RUMAH KACA (GRK) - Wardoyo Wardoyo (JMB : Jurnal Manajemen dan Bisnis, 2016)
Green house gases (GHG) in the atmosfer increase rapidly as a result of human activities such as the use of fossil energy for industry, power, and transportation, as well as the change of land uses for settlement, crop estates, buildings and others. Increase of GHG on air will rise temperature up, and change climate on earth. Scientific evidence indicated that climate change is a serious threat and needs urgent action. An increase in temperature for 2o celcius may cause a severe disaster such as flooding along shore lines and small islands, extinction of 15% - 40% species, and decrease of 20% agricultural products. GHG emissions can be reduced in several ways among other things are by decreasing demand on goods and services that causes intensive emissions, and avoiding activities that change land uses i.e., deforestation, estate crop development and mining. Markets for carbon trading are available in Tokyo, New York, Chicago, and this market encourages efficient GHG emission reduction. REDD is another scheme of carbon trading. In this scheme carbon emissions reduction from the forests will receive incentive/compensation (in financial value). However, the scheme is still in a process of development in global negotiation. This paper highlighted and described background on climate change, efforts toreduce GHG emissions, REDD scheme and problems in its implementation.